Acute Intraorbital Hemorrhage following Reduction of a Displaced Orbitozygomaticomaxillary Complex Fracture. Issue 3 (September 2015) - Susarla, SrinivasMurthy; Bojovic, Branko
Orbitozygomaticomaxillary complex (OZMC) fractures are commonly encountered by the craniomaxillofacial trauma surgeon and may, in fact, be the most common type of orbital fracture. Disruption of articulation with the frontal and sphenoid bones causes disruption of the internal orbital skeleton, which can result in diplopia from extraocular muscle swelling or entrapment, or enophthalmos from increased orbital volume. Although there is significant energy transferred to the orbit in these injuries, blindness and intraorbital hematoma are, fortunately, relatively rare complications, typically seen pre- or postoperatively. In this report, we describe the development of acute intraorbital hemorrhage following reduction of a displaced OZMC fracture.